Preventing Cesareans with Peanut Ball Use: A Clinical Findings - Outland, Lauren; Alvarado, Yolanda (Recent Updates in Disease and Health Research Vol. 6, 2024)
This study discusses the experiences with innovation dissemination and testing the PB’s effectiveness. Using a retrospective study design, with minimal time and cost, obstetrical units could assess the effectiveness of PB protocols and add their findings to the growing literature. To reduce the high number of cesarean births in the US, the Association of Women's Health Obstetrical and Neonatal Nurses (AWHONN) has started a Peanut Ball campaign. Because of their immobility and flexible pelvis, women who undergo epidural anesthesia are particularly prone to delivery by cesarean section. The peanut ball (PB) is a birthing ball that when placed between the mother’s legs can increase pelvic dimensions and facilitate fetal descent and birth. This study took place in an urban HMO hospital in Southern California that opted to use peanut balls (PBs) among laboring patients under epidural anesthesia. Using a retrospective study design that uses data collected for non-research purposes saves time and cost. Our retrospective study examined the difference in VDs with patient-controlled epidural anesthesia (PCEA) in the first five months of 2016 prior to PB use compared with the same months in 2017 post-intervention. Using a paired t-test we found a significant difference in successful PCEA vaginal births in 2016 compared to 2017 (p = .008). This retrospective study design can be easily replicated in other venues whose results could provide evidence for a simple inexpensive way to promote AWHONN’s campaign of preventing cesarean births.